Structure of the Pf12 and Pf41 heterodimeric complex of Plasmodium falciparum 6-cysteine proteins. (16th February 2022) - Dietrich, Melanie H; Chan, Li-Jin; Adair, Amy; Boulet, Coralie; O'Neill, Matthew T; Tan, Li Lynn; Keremane, Sravya; Mok, Yee-Foong; Lo, Alvin W; Gilson, Paul; Tham, Wai-Hong
Abstract: During the different stages of the Plasmodium life cycle, surface-associated proteins establish key interactions with the host and play critical roles in parasite survival. The 6-cysteine (6-cys) protein family is one of the most abundant surface antigens and expressed throughout the Plasmodium falciparum life cycle. This protein family is conserved across Plasmodium species and plays critical roles in parasite transmission, evasion of the host immune response and host cell invasion. Several 6-cys proteins are present on the parasite surface as hetero-complexes but it is not known how two 6-cys proteins interact together. Here, we present a crystal structure of Pf12 bound to Pf41 at 2.85 Å resolution, two P. falciparum proteins usually found on the parasite surface of late schizonts and merozoites. Our structure revealed two critical interfaces required for complex formation with important implications on how different 6-cysteine proteins may interact with each other. Using structure-function analyses, we identified important residues for Pf12-Pf41 complex formation. In addition, we generated 16 nanobodies against Pf12 and Pf41 and showed that several Pf12-specific nanobodies inhibit Pf12-Pf41 complex formation. Using X-ray crystallography, we were able to describe the structural mechanism of an inhibitory nanobody in blocking Pf12-Pf41 complex formation. Future studies using these inhibitory nanobodies will be useful to determine the functional role of these two 6-cys proteins in malaria parasites. Abstract : Malaria is a deadly disease that causes over 400 000 deaths worldwide. During its life cycle, malaria parasites exist in several forms across its different life stages and present diverse surface coat proteins as antigenic targets. One of the more abundant surface coat proteins of Plasmodium falciparum, the most lethal malaria parasite species, is the 6-cysteine protein family. Several members of this family are implicated in critical functions in fertilization, transmission, immune evasion and host cell invasion. Here, using structural biology, we provide an understanding on how two 6-cysteine proteins, Pf12 and Pf41 which are abundant blood stage merozoite proteins, bind to each other using interfaces between their respective 6-cysteine domains and is further anchored by an insertion of a Pf41 loop into the second 6-cysteine domain of Pf12. We found that nanobodies against Pf12 were able to block complex formation and structural analyses showed that a nanobody loop binds to a region, which normally binds the Pf41 insertion loop, thus resulting in steric hindrance in one of the critical interaction sites. Our study provides new structural insights on the 6-cysteine proteins that will be important to progress our understanding on how they function during the malaria parasite life cycle.